2020
DOI: 10.4103/jfmpc.jfmpc_187_20
|View full text |Cite
|
Sign up to set email alerts
|

Role of body visceral fat in hypertension and dyslipidemia among the diabetic and nondiabetic ethnic population of Tripura—A comparative study

Abstract: Background: Excess fat in the upper part of human body correlates with increased mortality and risk for diabetes, dyslipidemia, and hypertension. In India, there are very limited data available on the association of excess body visceral fat with hypertension and dyslipidemia independent of obesity and diabetes. Objective: The objective of this study is to assess the role of body visceral fat percentage in hypertension and dyslipidemia among diabetic and nondiabetic indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Many clinical and in vivo studies reported that blood pressure level is proportional to obesity or weight gain grade [ 13 15 ], moreover, the positive association between visceral fat percentage and hypertension was also reported in several researches [ 16 19 ].…”
Section: Discussionmentioning
confidence: 97%
“…Many clinical and in vivo studies reported that blood pressure level is proportional to obesity or weight gain grade [ 13 15 ], moreover, the positive association between visceral fat percentage and hypertension was also reported in several researches [ 16 19 ].…”
Section: Discussionmentioning
confidence: 97%
“…These factors contribute to insulin resistance and arterial stiffness [ 35 , 36 , 37 ]. Second, augmentation of visceral fat mass triggers an inflammatory response, resulting in the thickening of blood vessel walls, impediment of blood flow, and constriction of vascular passages [ 38 ]. The susceptibility of males to hypertension is further accentuated by lower skeletal muscle mass and higher adipose tissue content.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, men exceeded these limits more than women. Body fat percentage is strongly associated with risks of chronic diseases such as hypertension, dyslipidaemia, diabetes mellitus, and heart disease [ 49 ]. On the other hand, some studies have suggested that WHR combined with BMI may be a better indicator for evaluating the relationship between obesity and health [ 50 ].…”
Section: Discussionmentioning
confidence: 99%